Stress related necrotizing ulcerative gingivitis: A case report - Safaa, Boubdir; Wafa, El Kholti; Loubna, Rhalimi; Jamila, Kissa (Hasanuddin University, 2024)
Necrotizing ulcerative gingivitis (NUG) is a classic form of necrotizingperiodontal diseases. It has a rapid and aggressive onset with a multifactorialcomplex etiologysuch as stress, nutritional deficiencies, and immune system dysfunctions. Clinically, NUG is characterized by inflamedinterdental papillae,gingival necrosis, gingival pain, bleeding, and halitosis.Â The treatment of NUG included an initial phase that should be providedimmediately to stop disease progression and to controlpatientâ€™s feeling of discomfort and pain. The second phase of the treatment of the preexisting condition, then, the surgical correction of the diseasesequelae .After active therapy was completed; a periodontal maintenance regimen was established.Â The aim of this case report is to describe the diagnosis approach and treatment of NUG in a male patient with no systemic disease and probable mechanism of pathogenesis of predisposing factors involved